Synergistic Effects of Walking and Acupressure on Stroke Risk Reduction in Individuals with Hypertension and Diabetes Melitus - Leli Mulyati; Yanti Sutriyanti; Meigo Anugra Jaya; Raden Siti Maryam; Tri Endah Pangastuti (Jurnal Penelitian Pendidikan IPA, 2026)
Stroke is a leading cause of death and disability worldwide. Most strokes are associated with modifiable risk factors, such as hypertension, diabetes mellitus, and high cholesterol. These risk factors can be managed through non-pharmacological approaches, such as physical activity and complementary therapies. To analyze the effect of a combination of walking intervention and acupressure therapy on blood pressure, fasting blood glucose levels, and cholesterol levels in patients with stroke risk factors. Methods: This study used a quantitative method with a quasi-experimental two-group pretest–posttest design. A total of 60 respondents from the working areas of the Curup Community Health Center and the Perumnas Community Health Center were divided into an intervention group and a control group. The intervention group received a walking program combined with acupressure therapy and was monitored daily using a checklist. Blood pressure was measured using an Omron digital sphygmomanometer, while fasting blood glucose and cholesterol levels were measured using a Multimeter Auto Check device. Measurements were taken before the intervention and on the 12th day after the intervention. Data analysis used paired t-tests, Wilcoxon tests, and Mann–Whitney tests according to data distribution. Conclusion: There were significant differences in systolic blood pressure, fasting blood glucose levels, and cholesterol levels in the intervention group after the intervention (p < 0.001). However, changes in diastolic blood pressure did not show significant differences during the study period. The Mann–Whitney test also showed significant differences between the intervention and control groups in systolic blood pressure, fasting blood glucose, and cholesterol. Stroke prevention education has a positive impact on controlling stroke risk factors, particularly systolic blood pressure, fasting blood sugar, cholesterol, and knowledge levels. Health behavior monitoring using checklists has been implemented, but increased monitoring intensity is needed to support optimal clinical outcomes.